Evaluation of access to health care and its effects on health care utilization and health status of people with physical disabilities in Jigawa State, Nigeria - Zandam, Hussaini Umar (2017)
Introduction: Access to health care is a complex issue and has been a source of concern to policy makers and researchers. who continue to seek answers to fundamental questions about the relationship between access, healthcare utilization, and health status among vulnerable populations. There is growing body of evidence showing that across Low-income and Middle Income Countries, people with disabilities across sex and age groups have disproportionately higher unmet healthcare need that are associated with multitude access barriers and challenges that are prevalent among people with disabilities. Access to healthcare and other social services for people with disabilities is largely unexplored in Nigeria, however, the combination of political, cultural and socioeconomic factors mitigating against inclusion of people with disabilities and the generally weak healthcare system in the country may result in inequitable health and healthcare among people with disabilities. The objective of this study evaluate equity in access to healthcare services by comparing people with physical disability to their counterparts with no disability and examine the extent to which disparities in physical health between the two groups are associated with access to healthcare Methodology: This is a prospective ex post facto causal-comparative (explanatory) design to determine the differential effects of access to healthcare factors on healthcare utilization and health status between people with disabilities and their counterparts without disabilities. A multi-stage sampling method was used to recruit participants with physical disabilities who were cross-matched with participants without any disability based on age, gender and location. The study was conducted over a 6 months period where information on illness episodes and resulting healthcare seeking activities were used to evaluate healthcare utilization using Illness and healthcare seeking record (IR). Access to healthcare was evaluated from both subjective and objective perspective. Subjective measures were measured at the beginning of the study using self-evaluated access to health instrument across 6 dimensions including approachability, availability, accessibility, affordability, acceptability and accommodation. Objective measures of access were evaluated during the study including distance and travel time, expenditures related to healthcare seeking and waiting times were documented from healthcare seeking acts. A household questionnaire was used to collect information on socioeconomic characteristics of the participants at baseline. The physical component of Short Form (SF-8) health status instrument was used to measure physical health status at baseline and repeated measurements at 2, 4 and 6 months. Data analysis involved comparison between people with physical disabilities and counterparts without disability on bivariate and multivariate basis. Linear regression and multilevel modeling analyses were conducted to compare access to healthcare and healthcare utilization using SPSS software. Latent growth curve was used to model physical health trajectory and disparity was modeled using AMOS software. Result: The study shows that people with physical disability differs with their counterparts in several socioeconomic factors, perceived access dimensions and healthcare utilization as well as physical health overtime. The study also showed significant differences in perceived access reflecting largely socio-economic differences between people with physical disabilities and counterparts without disability (0.75, 0.41-0.056). Healthcare utilization was found to be significantly different even after adjusting for socioeconomic factors and access to healthcare (0.358, SE 0.030). However, results also show more heterogeneity of healthcare utilization access at district level due to access variables (0.308, SE 0.124) than at household level due to socioeconomic variables (0.154, SE 0.002). The study also finds that gap in physical health exists through out the study period. Result of the conditional effect of access factors on physical health after adjusting for healthcare utilization and socioeconomic factors shows that the difference in mean initial health between the disabled and non-disabled groups was reduced by 36% and the difference in mean rate of health change was reduced by 10%. The fit statistics (table suggest that the model fits the data well (RMSEA <0.05 and CFI > 0.95). The result shows that overall inequality in physical health between people with disabilities and counterparts without disability is influenced by access to healthcare as well as healthcare utilization and socioeconomic factors. Conclusion: People with physical disabilities were generally found to have a poor access to health care as they experience a number of barriers to needed health care. These barriers have a fundamental influence on health of people with disabilities. Increasing access to healthcare through inclusive health policy and organizational strategies should be a central focus of policy interventions for reducing differences in health among people with disabilities and larger population.